2016
DOI: 10.1097/mib.0000000000000657
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Fine

Abstract: Current results highlight the need to look beyond disease severity and examine the perception of functional disability of patients with IBD when seeking to identify youth at risk for internalizing symptoms such as depression and anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 32 publications
2
19
0
1
Order By: Relevance
“…Further, internalizing symptoms such as depression and anxiety are found to be independently associated with recurrence of IBD in adult population [1517]. The prevalence of depression varies anywhere between 13% in disease remission state to as high as 60% in patients with disease activity [38161819202122]. In our study, the prevalence of depression is estimated to be 13% amongst IBD patients and the single largest contributor of psychiatric disorders in our cohort followed by anxiety −12.7%.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Further, internalizing symptoms such as depression and anxiety are found to be independently associated with recurrence of IBD in adult population [1517]. The prevalence of depression varies anywhere between 13% in disease remission state to as high as 60% in patients with disease activity [38161819202122]. In our study, the prevalence of depression is estimated to be 13% amongst IBD patients and the single largest contributor of psychiatric disorders in our cohort followed by anxiety −12.7%.…”
Section: Discussionmentioning
confidence: 70%
“…Studies have shown the presence of internalizing symptoms is a strong predictor of health-related quality of life. Walter et al [16], reported that depression and anxiety are also associated with perceived functional disability in patients who are having clinical remission. Further, internalizing symptoms such as depression and anxiety are found to be independently associated with recurrence of IBD in adult population [1517].…”
Section: Discussionmentioning
confidence: 99%
“…The authors attributed this unexpected finding to the excellent social support in the young patients’ environment [ 41 ]. Walter et al [ 48 ], on the basis of a careful examination of the literature, noted that older studies (1989 – 2004) reported higher depression rates; subsequent advances in treatment may be responsible for the lower levels of psychological distress observed more recently. Therefore, we suggest that screening and treatment for mental wellbeing should be implemented especially for those with increased disease activity and potentially weaker social support.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of IBD on an adolescent patients' quality of life extends beyond their standard medical care. Adolescent patients with IBD are at an increased risk of depression and poor adherence to treatment plans [4][5][6]. This poor adherence exacerbates disease activity, results in lapses in care, and predisposes patients to preventable complications [7].…”
Section: Introductionmentioning
confidence: 99%